Long non-coding RNA AL139002.1 promotes gastric cancer development by sponging microRNA-490-3p to regulate Hepatitis A Virus Cellular Receptor 1 expression. Issue 1 (1st January 2021) - Chen, Yurong; Zhang, Renchao
ABSTRACT: Mounting evidence suggests that lncRNA regulates many important diseases. However, the biological role of most lncRNAs in gastric cancer (GC) remain unclear. In this paper, we determined differential expression of lncRNAs and predicted ceRNA networks in the GC database by bioinformatics analysis and validated in GC cells. The effect of lncRNA AL139002.1 on GC cells biological function was assessed by flow cytometry, CCK-8, colony formation, wound healing assay, transwell, western blot, and qRT-PCR. And the relationship of lncRNA AL139002.1 or HAVCR1 with miR-490-3p was verified by luciferase reporter assay. The results showed that lncRNA AL139002.1 was highly expressed in GC cells and lncRNA AL139002.1 knockdown induced apoptosis, while suppressed cell proliferation, migration, invasion, and EMT. Functional examining indicated that lncRNA AL139002.1 regulated HAVCR1 expression by competitively binding miR-490-3p. In addition, lncRNA AL139002.1/miR-490-3p/HAVCR1 regulated EMT and metastasis through MEK/ERK signaling. In conclusion, lncRNA AL139002.1 was highly expressed in GC cells, and lncRNA AL139002.1/miR-490-3p/HAVCR1 functioned critically in GC by regulating MEK/ERK signaling. Our findings demonstrated that lncRNA AL139002.1 served as a potential therapeutic and anti-metastatic biotarget for GC. Graphical abstract: uf0001